Globalisation Impact on the Western and Eastern Cultures - Khiltukhina, Evgenia (International Journal of Criminology and Sociology, 2021)
The investigation of the consequences of globalisation on the cultures of West and East is an important aspect in the study of modern world history. Technology and global commerce are rapidly developing, as a result of which, today, we can observe rapid cultural transformation. The aim of this paper is to study the impact of globalisation on the cultures of Western and Eastern countries. The author analyses how the globalisation affects each individual culture, and also models the possible ways of the world development, in the context of globalisation and the interaction of foreign cultures. The main research methods in this paper are: the comparative method, methods of analysis and synthesis of data, the historical method, and theoretical analysis of scientific literature on the topic, namely, globalisation and culture. The concepts of Western and Eastern culture were studied, the distinctive features of these cultures were analysed, as well as the religious prerequisites for the establishment of different worldviews. The results obtained in the course of the study will provide an opportunity to assess the prospects for the further development of Western and Eastern cultures in the modern world.